1985
DOI: 10.1111/j.1469-7610.1985.tb00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance, ‘Negativism’, and the Effects of Treatment Structure in Autism: A Naturalistic, Behavioral Study

Abstract: Nineteen autistic individuals were observed in their familiar residential environment using a time-sample technique. Rates of stereotyped and self-injurious behaviors, the direction of the subject's gaze (at staff, task or elsewhere) and the number of requests made to a subject by staff were a function of treatment structure, as defined by the staff: child ratio. While patterns of compliance in response to different types of requests were observed, subjects were generally compliant. The data do not support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…In line with the inhibitory account, several studies have reported that strong cues that may guide shifts of attention are associated with a reduced display of repetitive behaviour relative to situations in which no such structure is provided (Bartak & Rutter, 1973 ;Dadds et al, 1988 ;Olley, 1987 ;Schopler, Brehm, Kinsbourne, & Reichler, 1971 ;Volkmar, Hoder, & Cohen, 1985). In support of the generativity hypothesis, studies comparing the display of repetitive behaviour across settings consistently report that individuals with autism display the highest rates of repetitive behaviour when high demands are placed on their generative ability, either because they are alone and unoccupied, or because minimal cues are provided to guide behaviour (Charlop et al, 1983 ;Clark & Rutter, 1981 ;Dadds et al, 1988 ;Donnellan et al, 1984 ;Runco et al, 1986).…”
Section: Repetitive Behaviour As a Symptom Of Executive Dysfunctionmentioning
confidence: 89%
“…In line with the inhibitory account, several studies have reported that strong cues that may guide shifts of attention are associated with a reduced display of repetitive behaviour relative to situations in which no such structure is provided (Bartak & Rutter, 1973 ;Dadds et al, 1988 ;Olley, 1987 ;Schopler, Brehm, Kinsbourne, & Reichler, 1971 ;Volkmar, Hoder, & Cohen, 1985). In support of the generativity hypothesis, studies comparing the display of repetitive behaviour across settings consistently report that individuals with autism display the highest rates of repetitive behaviour when high demands are placed on their generative ability, either because they are alone and unoccupied, or because minimal cues are provided to guide behaviour (Charlop et al, 1983 ;Clark & Rutter, 1981 ;Dadds et al, 1988 ;Donnellan et al, 1984 ;Runco et al, 1986).…”
Section: Repetitive Behaviour As a Symptom Of Executive Dysfunctionmentioning
confidence: 89%
“…When the setting is less structured, greater differences are apparent between the groups, with the autistic children initiating fewer interactions and showing less attention to the social partner compared to matched controls (Kasari et al, 1993a). Many other findings attest to an increased social interest and responsiveness within more structured interactions (Clarke & Rutter, 1981;Dawson et al, 1990;Landry & Lx)veland, 1989;Volkmar, Hoder & Cohen, 1985). Thus the differences between the autistic children and the control children in their response to affect may be partially accounted for by a general difficulty in initiating interactions within unstructured social settings.…”
Section: Discussionmentioning
confidence: 99%
“…The over-arousal hypothesis is not supported by the observation that autistic individuals function most appropriately in highly structured situations (Voikmar, Hoder & Cohen, 1985). Similarly, although fixation times to social stimuli are shorter in autistic as compared to mentally retarded or normal control children (Hermelin & O'Connor, 1970), autistic subjects do not differ from retarded or normal children in visual preference for social stimuli (O'Connor & Hermelin, 1967).…”
Section: Explanations Of Gaze Deviance In Autism Have Centered Aroundmentioning
confidence: 98%